Constructive Theology, Black Liberation Theology, and Black Constructive Theology A History of Irony and Resonance - Wyman, Jason (2018)
Black liberation theology and Constructive theology have an inextricably intertwined history. Yet the shared history has been one full of tensions and ambiguity. Black Liberation theology and Constructive theology overlap in their concerns and their approaches. Most, but not all, Black liberation theology today is Constructive theology while all Constructive theology holds in sight liberationist aspirations, yet has not always succeeded in fully incorporating Black liberation theology. Understanding this relationship historically and conceptually is key to understanding the history of both. Liberation theologies, especially in their Black theological form, has pushed Constructive theology beyond a historically typical White liberal theological movement, a clear risk it ran in its origins. Likewise, Constructive theology has given Black theology, including liberationist ones, a space into which to grow and link up with other theological discourses.
Keywords: Black Liberation Theology; Black Theology; Constructive Theology; Workgroup on Constructive Theology